A Decade-Long Case Series Report on the Surgical Management of Complicated Umbilical Hernia in Patients with Decompensated Liver Cirrhosis Utilizing Incisional Negative Pressure Therapy - Miha Petrič; Danaja Plevel; Uroš Tršan; Blaž Trotovšek (Medicina)
Background and Objectives. Umbilical hernia is particularly common among patients with liver cirrhosis, affecting about 20% of this group, compared to 3–8.5% in healthy individuals. This increased prevalence is mainly due to weakened abdominal fascia, elevated intra-abdominal pressure, and malnutrition. The rapid progression of umbilical hernias often leads to complications such as skin necrosis, perforation, and strangulation. Historically, patients with liver cirrhosis and complicated umbilical hernia have faced high morbidity and mortality rates. However, recent advancements in perioperative management, especially in controlling ascites, have improved outcomes in elective treatments. Despite these advancements, managing patients with decompensated liver cirrhosis and complicated umbilical hernia in emergency settings remain a significant surgical challenge. Materials and Methods: We conducted a retrospective review of patients treated for complicated umbilical hernia at the University Medical Centre Ljubljana from 2015 to 2024, using prospectively collected data. This analysis involved implementing hernioplasty combined with incisional negative pressure wound therapy (iNPWT) as part of the surgical protocol. The primary endpoint of our study was the rate of local complications, while the secondary endpoints included the rate of systemic complications and 90-day mortality. Results: We treated 28 consecutive patients with complicated umbilical hernia and liver cirrhosis. Local wound complications were observed in three (10.7%) patients. Systemic complications developed in 10 patients (35.7%). The median duration of hospitalization was 8 days (range: 5–29), and no readmissions were recorded within the 30-day period. Two (7.1%) patients died within 90 days. Conclusions: Our experience indicates that iNPWT, when combined with surgical repair, can be safely utilized, yielding outcomes comparable to elective hernia repairs, even in emergency contexts. Further randomized controlled trials are necessary to validate these findings and optimize treatment protocols.